Evaluation of the JISC Information Environment: student perceptions - Jillian R. Griffiths (Information Research: An International Electronic Journal)
The Joint Information Systems Committee (JISC) Information Environment (IE, a development from the DNER - Distributed National Electronic Resource, is intended to help users in the UK academic sector maximise the value of published information resources by developing a coherent environment out of the confusing array of systems and services currently available. The EDNER Project (Formative Evaluation of the DNER) is funded to undertake ongoing evaluation of the developing IE over the full three years of the JISC 5/99 Learning & Teaching and Infrastructure Programme i.e. from 2000 to 2003. The EDNER Project is led by the Centre for Research in Library & Information Management (CERLIM) at the Manchester Metropolitan University; the Centre for Studies in Advanced Learning Technologies (CSALT) at Lancaster University is a partner. This paper reports on work in progress and some of the initial findings of the evaluation team.